Exploring English Teachers’ Views and Obstacles in Implementing Mobile Apps for Vocabulary Teaching - Andi Marhani; Munir; Nurdin Noni (International Journal of Language, Education, and Literature, 2025)
This research explores how English teachers perceive the use of mobile applications for vocabulary teaching at SMP Negeri 1 Wotu. Adopting a qualitative case study method, the study involved two English teachers, drawing data from interviews and classroom observations to capture their experiences with mobile-assisted learning tools. The findings indicate that both teachers view apps such as Quizizz and Kahoot as valuable for enhancing student engagement and making vocabulary lessons more dynamic and enjoyable. These platforms encourage active participation and motivation through gamified elements that align with students’ learning styles. Teachers observed increased enthusiasm and focus among students when digital tools were incorporated compared to traditional instruction. Despite these benefits, several challenges were identified that impede the effective use of mobile apps. Key obstacles included unreliable internet access, insufficient classroom resources, and disparities in students’ access to personal devices. Teachers also encountered technical issues when operating the apps and expressed uncertainty about their own digital preparedness, pointing to a lack of professional development. Furthermore, the assessment features within these apps were often limited to numerical feedback, offering little insight into deeper learning or language acquisition. The study concludes that while mobile apps show considerable promise for vocabulary teaching, their successful adoption depends on robust institutional support, improved infrastructure, well-designed implementation plans, and continuous teacher training. Addressing these factors is essential for ensuring that mobile-assisted vocabulary learning becomes a more inclusive and impactful practice in English classrooms.